Access, quality and equity in early childhood education and care: A South Australian study. (August 2015) - Krieg, Susan; Curtis, David; Hall, Lauren; Westenberg, Luke
While much is known about the factors related to student performance beyond Grade 3 less is known about the factors that are related to student performance in early childhood education and the early years in primary school. As part of the 'I go to school' project in South Australia, this study tracked children attending integrated preschool/childcare centres – known as Children's Centres – as they made their transition to school. Results indicated that children who attended early childhood education programs that were of higher quality – as characterised by higher staff qualifications and a greater range and more engaging children's activities – showed a greater gain in cognitive development than children who attended lower quality programs. Findings also suggested that children who benefitted the most from attendance in these programs were children from backgrounds of greater social disadvantage than children from less disadvantaged backgrounds.